Treatment of obstetric post-dural puncture headache. Part 1: conservative and pharmacological management. (May 2019) - Russell, R.; Laxton, C.; Lucas, D.N.; Niewiarowski, J.; Scrutton, M.; Stocks, G.
Highlights: Postnatal headache may be associated with maternal mortality. The management of obstetric post-dural puncture headache (PDPH) varies considerably. Much of the evidence on obstetric PDPH management is not of high quality. Evidence of obstetric PDPH treatment is reviewed and recommendations made. Women experiencing PDPH should be followed-up after hospital discharge. Abstract: The 2009–12 MBRRACE-UK report highlighted the deaths of two women in whom dural puncture had occurred during insertion of a labour epidural catheter. One woman received an epidural blood patch, the other did not, but both suffered with chronic headaches following discharge from hospital. Neither woman was adequately followed-up. Death resulted from a cerebral vein thrombosis in one case and a subdural haematoma in the other. Surveys of clinical practice in the UK have revealed significant variation in anaesthetic practice in the management of obstetric post-dural puncture headache. To help provide guidance on treatment, the Obstetric Anaesthetists' Association set up a working group to review the literature and produce evidence-based guidelines for management of obstetric post-dural puncture headache. These guidelines have been condensed into two review articles, the first of which covers conservative and pharmacological treatment.